Laminar burning velocities of H2/CO/CH4/CO2/N2 -air mixtures at elevated temperatures. (3rd May 2019) - Varghese, Robin John; Kolekar, Harshal; Kumar, Sudarshan
Abstract: The laminar burning velocity of nine different syngas compositions has been measured at elevated temperatures (350–650 K) for various equivalence ratios using an externally heated diverging channel method. The measured values are compared with the predictions of two detailed kinetic models (GRI 3.0 and FFCM-1). The predictions of FFCM-1 for various syngas (H2 /CO/CH4 /CO2 /N2 ) mixtures accurately capture the fundamental combustion characteristics, and GRI 3.0 mechanism overpredicts the laminar burning velocity for fuel rich syngas compositions. Temperature exponents mildly decrease with increase in equivalence ratio for mixtures investigated in the present work. Two correlations, one using linear regression, and another, a linear equation model is proposed to predict the laminar burning velocity accurately for various syngas compositional modifications. The developed linear model can be used for direct calculation of laminar burning velocities of different syngas compositions. Similarly, a temperature exponent correlation and its comparison with present measurements and simulations are also presented. The efficacy of the proposed models is evaluated through a detailed comparison with the literature. The model provides an excellent matching for following syngas compositions; 0.05 < X H 2 < 0.50, 0.08 < XCO < 0.50, 0 < X C H 4 < 0.13, 0 < X C O 2 < 0.50, 0 < X N 2 < 0.65, for an equivalence ratio of ϕ = 0.7–1.25, and mixture temperature from 300 to 650 K. Highlights: Burning velocities of 9 different compositions of syngas were measured at elevated temperatures. Quick approximation of laminar burning velocity of syngas-air mixtures. Two correlations based on the experimental measurements are proposed. Prediction by the proposed models is accurate for the compositional variability of syngas mixtures (H2 / CO/ CH4 / CO2 / N2 ).